2009
DOI: 10.1075/jlp.8.3.02arc
|View full text |Cite
|
Sign up to set email alerts
|

Parliamentary discourse in newspaper articles

Abstract: The present paper aims, first, at analysing how and why parliamentary debates are transformed into newspaper articles with a narrative-like format; and, second, at proposing a model for integrating this kind of material and analysis into a literacy-based language teaching programme. Our data consists of Greek parliamentary proceedings and newspaper articles on parliamentary debates. Based on the critical discourse analysis framework and the social constructionist paradigm, we support the claim that the linguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…3 It is exactly in this context that the present study sets out to investigate how liquid racism emerges from satirical news referring to migrants and targeting majority people for the racist ways they treat or perceive migrants. The texts examined here could be described not only as intended to produce humour but also as antiracist in the sense that they attempt to defend migrants and to denigrate racist values and practices prevailing among majority members (see among others van Dijk, 2021;Archakis & Tsakona, 2024a). Simultaneously, it will be demonstrated that humour resulting in or constituting liquid racism functions as a means of trivialising migrants and migrant-related affairs: it may create fictionalised contexts or represent social events in such a way that the humorous fictionalisation or representation ends up not only satirising racist majority members but also trivialising migrants' lives.…”
Section: From New Racism To Liquid Racismmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is exactly in this context that the present study sets out to investigate how liquid racism emerges from satirical news referring to migrants and targeting majority people for the racist ways they treat or perceive migrants. The texts examined here could be described not only as intended to produce humour but also as antiracist in the sense that they attempt to defend migrants and to denigrate racist values and practices prevailing among majority members (see among others van Dijk, 2021;Archakis & Tsakona, 2024a). Simultaneously, it will be demonstrated that humour resulting in or constituting liquid racism functions as a means of trivialising migrants and migrant-related affairs: it may create fictionalised contexts or represent social events in such a way that the humorous fictionalisation or representation ends up not only satirising racist majority members but also trivialising migrants' lives.…”
Section: From New Racism To Liquid Racismmentioning
confidence: 99%
“…This Section draws on extracts fromArchakis & Tsakona (2022;2024a) with appropriate modifications so as to suit the purposes of the present paper.…”
mentioning
confidence: 99%